Characterization of high-dose and high-energy implanted gate and source diode and analysis of lateral spreading of p gate profile in high voltage SiC static induction transistors. (March 2017) - Onose, Hidekatsu; Kobayashi, Yutaka; Onuki, Jin
Highlights: Appropriate dose of the p gate in the SIT is need for higher breakdown voltage than 100 V and good forward characteristics. The lateral spreading factor was about 0.5 for the p gate implanted higher than 1 MeV. The lateral spreading detrimentally affected the electrical properties of the SIT. Abstract: The effect of the p gate dose on the characteristics of the gate-source diode in SiC static induction transistors (SIT) was investigated. It was found that a dose of 1.5 × 10 14 cm −2 yields a pn junction breakdown voltage higher than 60 V and good forward characteristics. A normally on SiC SIT was fabricated and demonstrated. A blocking voltage higher than 2.0 kV at a gate-source voltage of −50 V and on-resistance of 70 mΩ cm 2 were obtained. Device simulations were performed to investigate the effect of the lateral spreading. By comparing the measured I - V curves with simulation results, the lateral spreading factor was estimated to be about 0.5. The lateral spreading detrimentally affected the electrical properties of the SIT made using implantations at energies higher than 1 MeV.